(untitled) (River Edge, NJ., 2004)
This proceedings volume explores the pathways and mechanisms by which constituent residues interact and fold to yield native biological macromolecules (catalytic RNA and functional proteins), how ribosomes and other macromolecular complexes self-assemble, and relevant energetics considerations.
Keywords: Macromolecules,Đại phân tử; Congresses,Hội thảo